Production of a novel fermented milk fortified with natural antioxidants and its analysis by NIR spectroscopy. Issue 1 (June 2015) - Aliakbarian, Bahar; Casale, Monica; Paini, Marco; Casazza, Alessandro Alberto; Lanteri, Silvia; Perego, Patrizia
Abstract: In this work the effect of the addition of aqueous phenolic extracts, from olive and grape pomace, to fermentation media of the skim milk was investigated with the aim to produce a novel functional product. Additionally, Near Infrared (NIR) spectroscopy was assessed as a rapid and alternative method to traditional identification methods for the characterization of the new product. Results herein indicated that phenolic compounds are stable during the fermentation and they did not interfere with the manufacturing process. By extracting the information contained in the NIR spectra using the multivariate analysis, it was possible to discriminate between samples of probiotic milk according to the type of extract added and to evaluate the 'stability' of the product confirming NIR spectroscopy as a valid support to classical analysis. We concluded that, after sensorial evaluation of the product, fermented milk fortified with natural antioxidants could be considered a novel functional dairy product with health beneficial properties. Highlights: Natural phenolic compounds were added in fermented milk during the fermentation. Total phenolics, antiradical power and bacterial viability were measured. Near Infrared spectra were in agreement with classic quantification methods. Phenolic compounds were stable during the fermentation.